2021
DOI: 10.3389/fpsyg.2021.679661
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Trust in University Management Among International Students During the COVID-19 Pandemic

Abstract: Since the end of 2019, the outbreak of the COVID-19 pandemic has engendered widespread fear and anxiety across China. Nearly half a million international students pursuing their studies in Chinese universities have also been exposed to the psychological distress triggered by the unfolding crisis. In addition to government and medical institutions' efforts, universities have also endeavored to mitigate concerns among these students under quarantine on campus by providing reliable information as well as medical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The management of the universities and colleges are seeking ways to improve the mental wellbeing of the students. In this regard, Khan et al examined the impact of trust in information provided by the university and the psychological wellbeing of the students ( 38 ). The findings suggested that trust in information significantly impacts the psychological wellbeing of college students.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The management of the universities and colleges are seeking ways to improve the mental wellbeing of the students. In this regard, Khan et al examined the impact of trust in information provided by the university and the psychological wellbeing of the students ( 38 ). The findings suggested that trust in information significantly impacts the psychological wellbeing of college students.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, evidence from mainland China shows that despite the challenges posed by the pandemic, trust in universities and their support (e.g. reliable information and monetary support) reduces mental health problems such as anxiety and depression among non-local students (Khan et al, 2021 ). Therefore, by addressing the three questions raised above, this study can lend support to existing research by offering insightful perspectives on stressors that are potentially more important to the well-being of non-local students during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Faced with the current pandemic, many young people are trying to find meaning in their lives, which implies rebuilding and committing to a new dynamic [ 34 ]. Recent studies showed that more than 30% of students experiencing stress, anxiety, depression, and fear of infection improved their resilience by getting involved in various activities such as physical exercise, recreational activities (watching TV series, reading storybooks, online and offline gaming and household chores) that helped them to cope with the situation better.…”
Section: Introductionmentioning
confidence: 99%